Thermal Stability and Acidity of Silica Supported Keggin Type Polyoxometalate K4[-SiW12O40]•nH2O - Welinda Me; Risfidian Mohadi; Aldes Lesbani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
Silica supported polyoxometalate K4[a-SiW12O40]·nH2O was prepared systematically using tetraethyl ortho silicate by sol gel method to form K4[a-SiW12O40]·nH2O/Si. Compound K4[a-SiW12O40]·nH2O/Si was characterized by diffraction, spectroscopic, and acidity analyses follow by thermal activity test at higher temperature up to 600 oC. Analysis of FTIR spectrum showed all unique vibration of polyoxometalate K4[a-SiW12O40]·nH2O was appeared at wavenumber 800-1000 cm-1 before and after supporting process. Crystallinity of K4[a-SiW12O40]·nH2O and K4[a-SiW12O40]·nH2O/Si were also similar without changing Keggin structure. Compound K4[a-SiW12O40]·nH2O/Si showed higher acidity than K4[a-SiW12O40]·nH2O probably due to Lewis acidity species. Keggin structure of K4[a-SiW12O40]·nH2O/Si was still retained up to 600 oC showing thermal stability of K4[a-SiW12O40]·nH2O/Si at high temperature.Keyword : Keggin polyoxometalate, tetraethyl ortho silicate, thermal stability, acidity